Kredibilitas sebagai Kontruksi Sosial Komunikasi dalam Mempengaruhi Komunikator pada Organisasi - Zalvi, Muhammad Azriel Ar Syahlaf; Abidin, Zainal; Susanto, Tri (Universitas Muhammadiyah Sumatera Utara, 2025)
This study analyzes the effect of the communicator credibility of the Chairman of BEM FISIP UNSIKA 2023 on board performance. Communicator credibility is measured through expertise, trustworthiness, and attractiveness. Using a quantitative approach and simple linear regression analysis on 58 board members, the results indicate that trustworthiness significantly influences performance, while expertise and attractiveness do not have a significant impact. These findings emphasize that effective leadership in student organizations is primarily determined by the board’s trust in its leader rather than other factors. The recommendation for student organization leaders is to build trust through transparent communication, responsiveness, and active engagement in organizational dynamics.Keywords: Communicator credibility, board performance, trustworthiness, leadership, student organization